2017
DOI: 10.1016/j.ceb.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial plasticity in the mammary gland

Abstract: Many epithelial tissues rely on multipotent stem cells for the proper development and maintenance of their diverse cell lineages. Nevertheless, the identification of multipotent stem cell populations within the mammary gland has been a point of contention over the past decade. In this review, we provide a critical overview of the various lineage-tracing studies performed to address this issue and conclude that although multipotent stem cells exist in the embryonic mammary placode, the postnatal mammary gland i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…Interestingly, the isolation and transplantation of fibroblasts from untreated mice was sufficient to promote some epidermal thickening and lineage infidelity, though to a significantly lesser degree than fibroblasts from Cisplatin-treated mice ( Fig.4I-L). This result suggests that the isolation procedure alone can prime the fibroblasts, as has been observed for other cell types 9,10 . Overall, we conclude that epithelial activation by DNA damaging agents is cell non-autonomous, and that dermal fibroblasts are both necessary and sufficient to drive this response ( Fig.S4C-D).…”
Section: Dermal Fibroblasts Are Necessary and Sufficient For The Epitsupporting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, the isolation and transplantation of fibroblasts from untreated mice was sufficient to promote some epidermal thickening and lineage infidelity, though to a significantly lesser degree than fibroblasts from Cisplatin-treated mice ( Fig.4I-L). This result suggests that the isolation procedure alone can prime the fibroblasts, as has been observed for other cell types 9,10 . Overall, we conclude that epithelial activation by DNA damaging agents is cell non-autonomous, and that dermal fibroblasts are both necessary and sufficient to drive this response ( Fig.S4C-D).…”
Section: Dermal Fibroblasts Are Necessary and Sufficient For The Epitsupporting
confidence: 67%
“…Lineage-tracing has shown that although the embryonic mammary gland develops from bipotent stem cells, postnatally each cell type is maintained by distinct unipotent progenitors [1][2][3][4] . Strikingly, however, the myoepithelial cells become highly plastic when dissociated from their native tissue 1,2,[5][6][7][8][9] , such that a single transplanted cell can regenerate a complete mammary ductal tree within the cleared fat pad of a recipient mouse 6,7 . A similar loss of fate restriction has been observed in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation potential of these cells -i.e., their ability to generate one or both of the mammary epithelial cell lineages -is an area of intense interest. Early population-based genetic fatemapping studies in the postnatal mammary gland generated conflicting results, providing evidence in support of both unipotent and bi/multipotent capacities of adult stem/progenitor cells under physiological conditions (for a detailed overview see Lloyd-Lewis et al, 2017;Seldin et al, 2017;Rodilla and Fre, 2018). Discrepancies between these studies may be, in part, attributable to the temporal and promiscuous labeling of cells by selected pathway-specific or lineage-specific promoters.…”
Section: Multidimensional Imaging Of Mammary Ductal Morphogenesismentioning
confidence: 99%
“…While recent genetic fate-mapping studies have demonstrated the unipotency of postnatal mammary lineage precursors in physiological conditions, the durable plasticity of these cells is becoming increasingly apparent (Seldin et al, 2017;Wahl and Spike, 2017;Rodilla and Fre, 2018). Unipotent precursors have been shown to reacquire multi-lineage differentiation capacity in transplantation assays (Stingl et al, 2006;Van Keymeulen et al, 2011;van Amerongen et al, 2012), in response to oncogenic induction (Liu et al, 2007;Koren et al, 2015;Van Keymeulen et al, 2015;Tao et al, 2017) and upon ectopic expression of critical fate determinants of the opposing lineage (Lilja et al, 2018;Wuidart et al, 2018).…”
Section: Multidimensional Imaging Of Mammary Ductal Morphogenesismentioning
confidence: 99%
“…The mammary gland is a highly ductal organ mainly composed of two distinct cell compartments, the epithelium, and the surrounding stroma, which are derived from ectoderm and mesoderm during embryogenesis [1][2][3] . Unlike most other epithelial organs, development of the mammary gland occurs postnatally [4][5][6] . Many signaling molecules such as growth hormone, estrogen, and growth factors stimulate formation and invasion of terminal end buds (TEB) to the mammary fat pad by regulating extracellular matrix (ECM) proteins 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%